Socks at War: American Hand Knitters and Military Footwear Production for the World Wars - Maines, Rachel P. (Studia Historiae Oeconomicae, 2019)
In both World Wars, combatant nations, including the United States, Britain, and Germany, learned that inadequate or poorly-maintained footwear produced costly and preventable casualties from trench foot and frostbite. While provision of shoes and boots to troops were major issues in earlier conflicts, no nation before World War I had fully appreciated the significance of warm, dry, well-fitting socks to the effectiveness of soldiers in the field. The large numbers of trench foot casualties in World War I, especially among the French and British, convinced policymakers that this vital commodity must receive a higher priority in military production planning, but few nations in wartime could shift production to knitting mills rapidly enough to make a difference. Thus, in Britain and the U.S, the best policy option proved to be recruiting women and children civilians to knit socks by hand for the military in the first war, and for refugees, prisoners and civilians in the second. This paper discusses the economic and military importance of this effort, including the numbers of pairs produced, and the program’s role in supplementing industrial production. The production of this low-technology but crucial item of military apparel is typical of detail-oriented tasks performed by women under conditions of full mobilization for war, in that they have a high impact on battlefield and home front performance and morale, but very low visibility as significant contributions to national defense. Often, both during and after the emergency, these efforts are ridiculed as trivial and/or wasteful. Unlike women pilots or industrial workers, handcrafters of essential supplies are regarded as performing extensions of their domestic roles as makers and caretakers of clothing and food. This was especially true in the U.S. in and after World War II, a wealthy industrialized nation that took pride in its modern - and thoroughly masculinist - military industrial complex.